Can reducing corporate income tax rates decrease tax avoidance? - Nugraha, Satria Yudha; Saud, Yehezkiel Victor; Firmansyah, Amrie (Educoretax, 2024)
This research aims to examine and analyze the effect of reducing corporate income tax rates on tax avoidance practices carried out by non-cyclical consumer sector companies. This research involves secondary data analysis using the Panel Data Regression approach with 6 research samples taken from the non-cyclical consumer sector on the LQ45 index for the 2018-2022 period. The total sample used in the study amounted to 30 observations based on purposive sampling. The test results show that reducing the corporate income tax rate positively and significantly affects tax avoidance practices in non-cyclical consumer sector companies on the LQ45 index. This research is expected to encourage the government to formulate other tax incentive policies and provide insights into the effectiveness of the implemented tax policies. One of the expected objectives of companies utilizing tax incentives is to accelerate the economic growth of society. Lower tax burdens are hoped to encourage companies to expand their businesses and potentially absorb more labor, triggering multiplier effects in the economic sector to advance public welfare. In terms of literature, this research contributes to enriching the discussion about the effect of reducing corporate tax rates on companies' tax avoidance, and it is expected to contribute to the development of tax accounting literature.